Functional Flow Cytometric Assay for Reliable and Convenient Heparin-Induced Thrombocytopenia Diagnosis in Daily Practice - Brigitte Tardy-Poncet; Aurélie Montmartin; Michele Piot; Martine Alhenc-Gelas; Philippe Nguyen; Ismail Elalamy; Andreas Greinacher; Emmanuel De Maistre; Dominique Lasne; Marie-Hélène Horellou; Grégoire Le Gal; Thomas Lecompte; et al. (Biomedicines, 2021)
Reliable laboratory diagnosis of heparin-induced thrombocytopenia (HIT) remains a major clinical concern. Immunoassays are highly sensitive, while confirmatory functional tests (based on heparin-dependent platelet activation) lack standardization. We evaluated the diagnostic performance of a functional flow cytometric assay (FCA) based on the detection of heparin-dependent platelet activation with an anti-p-selectin. A total of 288 patients were included (131 HIT-positive and 157 HIT-negative) with a HIT diagnosis established by expert opinion adjudication (EOA) considering clinical data and local laboratory results. The FCA was centrally performed in a single laboratory on platelet-rich plasma, using a very simple four-color fluorometer. The results were standardized according to the Heparin Platelet Activation (HEPLA) index. The serotonin release assay (SRA) was performed in the four French reference laboratories. Based on the final HIT diagnosis established by EOA, the sensitivity and specificity of the FCA were 88 and 95%, respectively, values very similar to those of the SRA (88 and 97%, respectively). This study showed that the FCA, based on easily implementable technology, may be routinely used as a reliable confirmatory test for HIT diagnosis.